2015
DOI: 10.1111/jvp.12227
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an extended‐release formulation of ceftiofur crystalline‐free acid in koi (Cyprinus carpio)

Abstract: The use of an extended release ceftiofur crystalline-free acid formulation (CCFA, Excede For Swine(®) , Pfizer Animal Health) in koi was evaluated after administration of single intramuscular (i.m.) or intracoelomic (i.c.) doses. Twenty koi were divided randomly into a control group and four treatment groups (20 mg/kg i.m., 60 mg/kg i.m., 30 mg/kg i.c., and 60 mg/kg i.c.). Serum ceftiofur-free acid equivalents (CFAE) concentrations were quantified. The pharmacokinetic data were analyzed using a nonlinear mixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 35 publications
(49 reference statements)
0
6
0
Order By: Relevance
“…Flip-flop kinetics for CFFA has been observed in multiple species as compared to immediate-release formulations, including lowerorder species such as green iguana and koi (Cyprinus carpio). 12,23,31 In examining the disposition of ceftiofur equivalents over time, each animal in this study was found to have a variable small secondary peak in drug concentrations at one time point between 120 and 366 h postdose following a decline in drug concentrations. This may represent variable absorption rates of long-acting ceftiofur formulations.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Flip-flop kinetics for CFFA has been observed in multiple species as compared to immediate-release formulations, including lowerorder species such as green iguana and koi (Cyprinus carpio). 12,23,31 In examining the disposition of ceftiofur equivalents over time, each animal in this study was found to have a variable small secondary peak in drug concentrations at one time point between 120 and 366 h postdose following a decline in drug concentrations. This may represent variable absorption rates of long-acting ceftiofur formulations.…”
Section: Discussionmentioning
confidence: 89%
“…5,13 Drug administration and sample collection A 30-mg/kg dose of CCFA (Excede w 200 mg/ml, Zoetis) was administered intramuscularly in the left triceps muscle of each individual. Up to 1 ml of whole blood was collected from the lateral occipital sinus before injection (Time 0), and at 4,12,24,48,72,120,144,192,288, and 366 h postinjection. Blood was placed directly into lithium heparin tubes and kept at room temperature for transport to the laboratory for plasma separation.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was similarly short in tilapia when CS was examined in the fish (Khalil et al., 2016). In contrast to the highly water‐soluble chemical form of CS used in this study, the t 1/2 was extremely long (583.8 hr) when a water‐insoluble formula (ceftiofur free base) was injected to koi carp (Grosset et al., 2015). It would be reasonable to ascribe the striking difference to body residence time of the drug between koi (Khalil et al., 2016) and olive flounder or tilapia to the chemical formula, rather than to fish species.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacokinetic profiles of CS or its base form (ceftiofur) have been assessed in various livestock animals such as dairy cows, horses, sheep, camels and deer (Craigmill et al., 1997; Drew et al., 2004; Foster et al., 2016; Fultz et al., 2015; Garrett et al., 2015; Goudah, 2007; Rivera‐Garcia et al., 2014; Wang, 2015). In contrast, pharmacokinetic information in fish species is rare reports being available only from tilapia and carp (Grosset et al., 2015; Khalil et al., 2016; Somjetlertcharoen, 2001).…”
Section: Introductionmentioning
confidence: 99%